2015
DOI: 10.3748/wjg.v21.i26.8118
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of endoscopic ultrasonography-guided fine needle aspiration for pancreatic neuroendocrine tumor grading

Abstract: AIM:To evaluate the efficacy of endoscopic ultrasonography-guided fine needle aspiration (EUS-FNA) for grading pancreatic neuroendocrine tumors (PNETs). In the two cases treated with chemotherapy, the effects and prognoses were evaluated. METHODS: RESULTS:The sampling rate for histological diagnosis by EUS-FNA was 100%. No adverse effects were observed. The concordance rate between specimens obtained by EUS-FNA and surgery was 87.5% (7/8). For the two cases treated with chemotherapy, case 1 received somatostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 29 publications
0
35
0
1
Order By: Relevance
“…6 Hasegawa et al showed a higher intratumoral dispersion of Ki-67 in grade 2 tumors, and found a concordance rate between EUS-FNA and resected specimens of 74% using the mean Ki-67 index and 77.8% using the highest Ki-67 index. 20 They found discordances only in G1-G2 tumors. 2 McCall et al used digital image analysis software to analyze mitotic rate and Ki-67 index in cytological samples with >500 tumor cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…6 Hasegawa et al showed a higher intratumoral dispersion of Ki-67 in grade 2 tumors, and found a concordance rate between EUS-FNA and resected specimens of 74% using the mean Ki-67 index and 77.8% using the highest Ki-67 index. 20 They found discordances only in G1-G2 tumors. 2 McCall et al used digital image analysis software to analyze mitotic rate and Ki-67 index in cytological samples with >500 tumor cells.…”
Section: Discussionmentioning
confidence: 97%
“…17 Sugimoto et al showed a concordance rate of 87.5%. 20 They found discordances only in G1-G2 tumors. Fujimori et al observed that 89.2% of cases had a Ki-67 index concordant between histology and cytology, and suggested that tumor size and main pancreatic duct obstruction could be helpful in the identification of G2-G3 tumors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Specific ultrasonographic features allow distinction between pancreatic carcinomas and neoplasms of neuroendocrinal origin, as well as between functional and nonfunctional tumours [6,87]. The usefulness of EUS in the assessment of staging has also been confirmed, particularly for the evaluation of vascular invasion and tumour staging [6,88,89].…”
Section: Endoscopic Ultrasonographymentioning
confidence: 99%
“…Feinnadelpunktaten (FNP) von Pan-NEN eingesetzt werden kann [10,23,59,72]. Bei den G3-Tumoren, welche je nach Lokalisation ca.…”
Section: Ki-67-immunhistochemieunclassified